Phenophase wise study of parameters controlling water requirement of soybean crop [Glycine max (L.) Merr.] at various agroclimatic zones (MAUSAM, 2012)
Soybean is a major kharif season crop in parts of M.P., U.P., Gujarat, Punjab and Haryana,Maharashtra, Rajasthan, A.P. and Chattisgarh. The present work was undertaken to study the parameters controllingwater requirement of the crop at various phenophases in soybean growing 8 ET- stations (viz., Akola, Bangalore,Banswara, Dharwar, New Delhi, Parbhani, ICRISAT and Rahuri) in various agroclimatic zones. Eight phenophases of thecrop (viz., germination, seedling, vegetative, active vegetative, flowering, pod formation, pod maturity and harvesting)were identified. The data were collected for latest available 3 to 5 years and the mean values were analysed. The study onsoybean crop revealed that the mean total water requirement demand of the crop varied from 294.7 to 559.2 mm indifferent soybean growing ET stations. The ET demand reached the peak mostly at active vegetative stage (which was19.0 to 25.6 % of the total ET demand, at various locations). The computed best – fit ET curves provide ET demand ofthe crop at any point of the phenophases for the specific location. The rainfall during study period was mostly sufficientto meet the crop specific ET demand at various phenophaes of soybean crop. Abundant soil moisture supported goodvegetation cover. The mean Kc value varied widely from 0.61 to 0.98 among different stations studied, which reachedtheir peak mostly at active vegetative to flowering stages, where the values were even more than 1 in most of thosephenophases except 3 stations. The mean soybean crop yield and productivity varied widely agroclimatic zone wise. Thesoybean yield varied from 981.0 kg/ha to 2530.6 kg/ha, while productivity per day varied from 9.0 kg/ha/day to 23.2kg/ha/day. The WUE of the crop laid between 2.1 kg/ha/mm to 6.0 kg/ha /mm at various locations.